Externalized Glycolytic Enzymes Are Novel, Conserved, and Early Biomarkers of Apoptosis - Ucker, David S. (American Society for Biochemistry and Molecular Biology, 2012)
The intriguing cell biology of apoptotic cell death results in the externalization of numerous autoantigens on the apoptotic cell surface, including protein determinants for specific recognition, linked to immune responses. Apoptotic cells are recognized by phagocytes and trigger an active immunosuppressive response (“innate apoptotic immunity” (IAI)) even in the absence of engulfment. IAI is responsible for the lack of inflammation associated normally with the clearance of apoptotic cells; its failure also has been linked to inflammatory and autoimmune pathology, including systemic lupus erythematosus and rheumatic diseases. Apoptotic recognition determinants underlying IAI have yet to be identified definitively; we argue that these molecules are surface-exposed (during apoptotic cell death), ubiquitously expressed, protease-sensitive, evolutionarily conserved, and resident normally in viable cells (SUPER). Using independent and unbiased quantitative proteomic approaches to characterize apoptotic cell surface proteins and identify candidate SUPER determinants, we made the surprising discovery that components of the glycolytic pathway are enriched on the apoptotic cell surface. Our data demonstrate that glycolytic enzyme externalization is a common and early aspect of cell death in different cell types triggered to die with distinct suicidal stimuli. Exposed glycolytic enzyme molecules meet the criteria for IAI-associated SUPER determinants. In addition, our characterization of the apoptosis-specific externalization of glycolytic enzyme molecules may provide insight into the significance of previously reported cases of plasminogen binding to α-enolase on mammalian cells, as well as mechanisms by which commensal bacteria and pathogens maintain immune privilege.